Comparison of geometric design, metallurgical features and mechanical behavior of ProTaper Gold SX and two replica-like instruments - Martins,Jorge N.R. (2021)
Abstract Objectives: To assess the characteristics, performance, and safety of ProTaper Gold SX (PTG SX) replica-like instruments. Methods: A multimethod research involving the assessment of geometric design (macro and through scanning electron microscope), Ti/Ni proportions (energy-dispersive X-ray spectroscopy), phase transformation temperatures (differential scanning calorimetry), torsional resistance, and flexibility was conducted to compare two SX replica-like instruments (Premium Taper Gold and Go-Taper Flex) with the original PTG SX. Results were compared using one-way ANOVA with post hoc Tukey or Kruskal-Wallis tests according to gaussian or non-gaussian distribution (Shapiro-Wilk test). The significance level was set at 0.05. Results: The three SX instruments have nine cutting blades with helix angles of approximately 21o, symmetrical blade geometry without radial lands, a convex triangular cross-section design, and near equiatomic Ti/Ni atomic proportions. Design differences were observed at the tip geometry and surface finishing, which was smoother in the Premium Taper Gold and irregular in the Go-Taper Flex. Distinct R-phase start (Rs) and finish (Rf) phase transformation temperatures were noted between PTG (Rs ~48oC and Rf ~30oC), Go-Taper Flex (Rs ~43oC and Rf ~25oC), and Premium Taper Gold (Rs ~30oC and Rf ~15oC). In the mechanical tests, Go-Taper Flex presented lower maximum torque (mean 0.5 N.cm) and higher bending resistance (mean 582.2 gf) (less flexibility) than PTG (means 0.8 N.cm cliniand 447.1 gf) (P<0.05). No significant differences were observed in the mechanical tests between Premium Taper Gold and PTG (P>0.05). Conclusions: Overall, the tested replica-like systems showed different features compared to the original PTG SX instrument.